Pengembangan Soal Matematika Model Pisa untuk Mengukur Kemampuan Penalaran Matematika - Rosalina, Elya; Elly S, As (JOEAI (Journal of Education and Instruction), 2018)
The purpose of the study was to develop a mathematical problem of the PISA model to measure the mathematical reasoning ability of students of the Lubuklinggau City Middle School. This research is a development research or development research type formative research. This research was conducted through two stages, namely pleminary and formative evaluation stages which included self evaluation, expert reviews and one-to-one (low resistance to revision) and small groups and field tests (hight resistance in revison). The data analysis technique used in this study was descriptive data analysis. The results of the research, based on the development process obtained, the prototype of the question set developed has a potential effect, this can be seen from the results of tests that have been given with an overall average score of 61.09 which shows that students' mathematical reasoning abilities are included in both categories with a scale of categories well it is 61 - 80. Conclusions, the development of PISA mathematical problems is able to measure students' mathematical reasoning abilities. Keywords: Questions, PISA, Ability, and Reasoning